Las instrucciones de los diputados orientales a la Asamblea del Año XIII - Frega Novales, Ana (Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2013)
The article analyzes the instructions given to the deputies of the emerging Oriental Province in 1813 as an expression of the exercise of “individual sovereignty of the people” proclaimed by Artiguism. Through the comparison of the different versions, this work seeks an approach towards the local reception, appropriation and reworking of the ideas regarding the construction of a new political order in the River Plate.